The Effect of Education Using Leaflet Media About Prevention of Anemia During Menstruation on the Knowledge of Young Girls at SMP 19: Pengaruh Edukasi Menggunakan Media Leaflet Tentang Pencegahan Anemia Saat Menstruasi Terhadap Pengetahuan Remaja Putri di SMP 19 - Hadina Hadina; Sri Restu Tempali; Ni Nyoman Etik Erlawati (Napande: Jurnal Bidan, 2022)
ABSTRACT Anemia is a condition where the level of hemoglobin (HB) in the blood is lower than normal. Blood women suffer from anemia from 37.1% in 2013 to 39.1% in 2018. Menstruation is one of the factors that cause anemia at this time women lose a lot. SMP 19 Palu has never received education about preventing anemia during menstruation which affects the knowledge of adolescent girls in an effort to prevent anemia. This study aims to analyze the effect of education using leaflets about preventing anemia during menstruation on the knowledge of adolescent girls at SMP 19 Palu. This research method is Pre Experiment with One Group Pretest Posttest Design, the research population is all students of class VII, VIII, IX, totaling 125 students. The sample in this study were 35 female students. Sampling was done by Simple Random Sampling. The results of the pre-test were only one person with good knowledge and 24 people with sufficient knowledge. In the post test 31 people with good knowledge and 4 people with sufficient knowledge got a score of 17.50 and a p-value of 0.000. can: education using leaflets can improve adolescent girls about preventing anemia during menstruation. It is recommended that the school provide education using leaflet media to increase knowledge of preventing anemia during menstruation.